Public Relations Strategy of Kedai Kopi Chuseyo with Korean Wave Identity in Building a Contemporary Image - Denny Limanto; Christina Christina; Rustono Marta; Laurencia Kurniawati (2021)
Coffee business industry is growing rapidly due to changes in the lifestyle of the Indonesian people. Based on research, coffee shops in Indonesia as of August 2019 reached 2,950 coffee shops. The breaker of the contemporary coffee concept influenced by the Korean Wave is Kopi Chuseyo. The purpose of this research is to identify the Public Relation strategies used by Kopi Chuseyo in building its image and to see its image in the viewpoints of consumers. The research method used is qualitative, in the form of a case study with a descriptive analysis approach. Data collection techniques used are observation, documentation and interviews. The results showed that Kopi Chuseyo managed to get a good corporate image in the eyes of the community by involving the community, organizing events, and using social media. Kopi Chuseyocan be categorized into five types of brand images, namely mirror image, current image, wish image, corporate image, and multiple image. These types are responded by customers after going through the stages of cognition, perception, attitude and motivation.